Conducting scaffold supported defect rich 3D rGO-CNT/MoS2 nanostructure for efficient HER electrocatalyst at variable pH. (1st February 2022) - Bolar, Saikat; Shit, Subhasis; Samanta, Pranab; Chandra Murmu, Naresh; Kolya, Haradhan; Kang, Chun-Won; Kuila, Tapas
Abstract: Designing a suitable noble metal-free electrocatalyst for the hydrogen evolution reaction (HER) is enduring challenge. Molybdenum disulfide (MoS2 ) shows structural and electronic advantages as potential HER electrocatalyst. The structural and electronic design of MoS2 electrocatalysts should be considered to improve the efficiency and stability of MoS2 based electrodes. This report shows that the presence of synergistic interaction significantly improves the HER electrocatalytic activity of defect-rich 3D rGO-CNT/MoS2 composites. The Defect-rich conductive scaffold supported nanostructures can improve the catalytic performance and stability. Lowering of the HOMO-LUMO gap supervises the charge transfer resistance of the nanostructure. The turnover frequency value indicates that 3D rGO-CNT/MoS2 acts as the potential electrocatalyst and the overpotential observed at a current density of 10 mA cm −2 in acidic and alkaline media are 88 mV and 172 mV, respectively. This investigation provides a new idea to develop molybdenum disulfide and scaffolds based 3D nanostructures to improve the inherent electrocatalytic activity of HER. Graphical abstract: Image 1 Highlights: Synthesis of conducting scaffold supported 3D rGO-CNT/MoS2 nanostructure. Physicochemical analysis leads to defect rich nanostructure with different S/Mo ratio. Formation of conducting scaffold based nanocomposite enhance HER activity. 3D nanostructure provide extra operational stability in acidic and alkaline pH.